How to correct student's oral errors in an EFL classroom - González Rivas, Guillermo Antonio; Henríquez Rivera, Ever Alexis; Martínez Herrera, José Douglas (2024)
Errors are the everyday opportunities that teachers can take advantage of to know what topics or structures need to be reinforced or reviewed while working in an EFL classroom. Teaching English to teens is a challenge while they are in the teaching-learning process with different interests and needs, so teachers have to look for ways of motivating them to keep on participating actively in a class while teens are getting involved and interested in the acquisition of the Second Language. English learners are surely going to make errors when expressing some ideas. They have to be treated not as something bad that shows students weakness, but as paths or ways to avoid while speaking. Teachers need to focus not on the errors that are made, but instead, they have to pay attention to the things behind the errors. That means that special attention have to be put to the things or sources that can make those errors happen during the process. Correcting mistakes is something that some teachers could not consider important in an EFL classroom, but this work has been made upon the belief that this is necessary to get students proficiency while speaking English. To do that some error correction techniques are presented with the purpose of giving readers some choices to be used while facing oral errors in an EFL classroom made up of EFL students